ECONOMIC AND LEGAL ASPECTS OF IMPLEMENTING THE PRACTICE OF THE ECHR IN THE NATIONAL JUDICIAL SYSTEM OF UKRAINE (CRIMINAL AND CIVIL CASES) - Anastasiia Pidgorodynska; Olha Polunina; Oleg Pushkar (Baltic Journal of Economic Studies)
Implementing the decisions of the European Court of Human Rights (ECHR) within Ukraine’s national judicial system, particularly in criminal and civil proceedings, is a pressing issue in the context of the country’s European integration and ongoing legal reforms. Despite Ukraine's formal commitments under the European Convention on Human Rights, systemic deficiencies, including chronic underfunding of enforcement institutions, continue to undermine compliance. This has resulted in mounting financial liabilities, encompassing compensation payments and reputational costs, thereby imposing a substantial strain on the state budget. The relevance of the study lies in the growing economic consequences of Ukraine's non-compliance with ECHR decisions, especially in cases of systemic violations such as Burmich and Others v. Ukraine, which exposed institutional failures in executing domestic judgments. The objective of this research is to conduct a comprehensive economic and legal analysis of the implementation of ECHR decisions in Ukraine, with a focus on criminal and civil justice. The objective of the present study is twofold: firstly, to identify the key economic risks and institutional shortcomings affecting compliance, and secondly, to propose reforms to mitigate these risks and shortcomings. The methodology employed is founded upon the principles of the comparative legal method, formal logical analysis, and systemic-structural approach. The examination encompasses national legislation, case law, and international best practices. The results of the study demonstrate that the primary barrier to effective implementation is the lack of dedicated budgetary funding, despite recent efforts by the Ministry of Justice to improve enforcement. The article concludes that it is essential for sustainable reform that legal obligations are aligned with financial planning.